Evaluasi Penjadwalan Proyek Produksi Conveyor Table Top Chain pada CV. XYZ dengan Pendekatan CPM - Saputro, Erwin; Siti Muhimatul Khoiroh (SURYA TEKNIKA, 2025)
This study evaluates the effectiveness of project scheduling for conveyor table top chain production at CV. XYZ using Critical Path Method (CPM). The study was motivated by frequent project delays in 2024, causing late deliveries and cost overruns. CPM identified the critical path as activities A–B–C–E–F–G–H–I–J–K–L–M–N, with one activity (Incoming Check Material) having slack. CPM estimated the project duration at 127 days of on-time completion. The findings show that CPM methode significantly improves time efficiency in project execution.